10th Anniversary of Actuators (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This is a reprint of the articles from the Special Issue entitled "10th Anniversary of Actuators", published in the open-access journal, Actuators. It consists of 18 representative works with four main topics: systematic reviews for specific types of actuators, performance evaluation, design and controls, and new actuators' applications. This reprint helps readers to understand the challenges and the trends of research and development in advancing the theories, methodologies, and design tools of actuators.